2007
DOI: 10.1002/rra.1008
|View full text |Cite
|
Sign up to set email alerts
|

Low potential for restraint of anadromous salmonid reproduction by beaver Castor fiber in the Numedalslågen River catchment, Norway

Abstract: After a long absence, beaver Castor fiber are rapidly returning to Europe. Their dam-building and tree-felling behaviour may have consequences for salmon Salmo salar and sea trout Salmo trutta management. In 2003 we investigated the parallel use of stream sections by beaver, sea trout and salmon and determined the potential hindrance that beaver dam-building presented for reproducing salmon and sea trout along 65 km of the Numedalslågen River and tributaries, a major Norwegian catchment. We also surveyed lando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…In the North‐western United States, beaver dams represent temporary structures often washed out during the same freshets used by Pacific salmon species to reach their spawning grounds (Taylor 1999). In Norway, it is suggested that any impacts of beaver dams on the upstream and downstream movements of Atlantic salmon and sea trout would be negligible because of their low density, small size and short life‐span (Parker and Ronning 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the North‐western United States, beaver dams represent temporary structures often washed out during the same freshets used by Pacific salmon species to reach their spawning grounds (Taylor 1999). In Norway, it is suggested that any impacts of beaver dams on the upstream and downstream movements of Atlantic salmon and sea trout would be negligible because of their low density, small size and short life‐span (Parker and Ronning 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In Norway, Atlantic salmon are thought to primarily spawn in the main Numedalslågen river, recolonized by beaver in 1957, while sea trout tend to utilize tributary streams (Parker and Ronning 2007). As a result, the impact of beaver activity on access to spawning grounds of the two salmonid species may differ substantially.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But just few countries had studies about that topic, e.g. Canada, USA, Germany, Lithuania (Naiman et al, 1988;Nummi, 1989;Balciauskas et al, 2001;Halley & Lamberg, 2001;Dalbeck et al, 2007;Parker & Rønning, 2007;Dalbeck & Weinberg, 2009;Hill & Duval, 2009). The majority of research about beaver's influence concerns North American populations of Castor canadensis (Baker & Hill, 2003;Gallant et al, 2004;Westbrook et al, 2006;Hood & Bayley, 2008;Karraker & Gibbs, 2009;Hood & Larson, 2014;Anderson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%